2016
DOI: 10.18632/oncotarget.7709
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care test for cervical cancer in LMICs

Abstract: Cervical cancer screening using Papanicolaou's smear test has been highly effective in reducing death from this disease. However, this test is unaffordable in low- and middle-income countries, and its complexity has limited wide-scale uptake. Alternative tests, such as visual inspection with acetic acid or Lugol's iodine and human papillomavirus DNA, are sub-optimal in terms of specificity and sensitivity, thus sensitive and affordable tests with high specificity for on-site reporting are needed. Using proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Western blot analysis was performed according to Mohammed et al12 To extract protein from cell lines, lysis buffer was added to cultured cells at 75% confluence and protein was transferred to tubes and centrifuged. The protein concentration for each sample was determined using the Pierce bicinchoninic acid (BCA) Protein Assay Kit (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed according to Mohammed et al12 To extract protein from cell lines, lysis buffer was added to cultured cells at 75% confluence and protein was transferred to tubes and centrifuged. The protein concentration for each sample was determined using the Pierce bicinchoninic acid (BCA) Protein Assay Kit (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…A global review by Kouliopoulos et al [ 8 ] of studies conducted between 1992 and 2015 showed that HPV testing has higher sensitivity and specificity than those of conventional cytology methods and allows for less frequent screening. When provided at point-of-care, patients receive their results in a shorter time frame (60-90 minutes on average, compared to up to 2 weeks for Pap smears) allowing for faster turnaround, more timely treatment, and reduction in patients lost to follow-up [ 4 , 9 , 10 ]. Research from Goldie et al [ 11 ] demonstrated that HPV-based screening for women once they have reached 35 years of age potentially reduces the lifetime risk of cervical cancer by 36%.…”
Section: Introductionmentioning
confidence: 99%
“…Such disproportion is likely due to the difficulties in the implementation of a cytology-based screening program, which requires multiple-day, long-distance visits and important human and financial resources [2]. The availability of Point-of-Care technologies and visual inspection methods is progressively changing our understanding of CC screening and giving way to the possibility of offering screening and, if needed, treatment in a 1-day session [3, 4]. This same-day screen-and-treat strategy has proven to be more effective than cytology-based screening in terms of both patient compliance and costs [5].…”
Section: Introductionmentioning
confidence: 99%